# If x = a (cos t +

x = a (cos t + t sin t)

Differentiating w.r.t t-

We need to make use of product rule to find derivative of t sin t

= a (-sin t +t cos t +sin t)

= at cos t ------- (i)

Again differentiating w.r.t t using product rule we get -

= a (Cos t – t Sin t)

y = a (sin t – t cos t)

Differentiating w.r.t t

We need to make use of product rule to find derivative of t cos t.

= a (Cos t - t (- Sin t) - Cos t)

= a (Cos t + t Sin t – Cos t)

= at Sin t ------- (ii)

Again differentiating w.r.t t using product rule we get -

Dividing the equation (ii) by equation (i)

Differentiating w.r.t x applying chain rule-

{using equation i}

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses